CHRONIC URTICARIA AND THE ROLE OF DIET : A SYSTEMATIC REVIEW - Siska, Siska (Cahaya Ilmu Bangsa Institute, 2024)
Background: Patients with chronic urticaria (CU) frequently inquire about dietary modifications. According to research, certain dietary adjustments may be beneficial to a subset of patients. Immunological food reactions are uncommon, but probable triggers of CU include those encountered in specific situations, such as people with a history of tick bites, raw or marinated fish intake, or celiac disease. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SCIENCE DIRECT, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 34 articles, whereas the results of our search on SCIENCE DIRECT brought up 16 articles. The results of the search conducted for the last year of 2014 yielded a total 12 articles for PubMed and 4 articles for SCIENCE DIRECT. In the end, we compiled a total of 5 papers, 4 of which came from PubMed and 1 of which came from SCIENCE DIRECT. We included five research that met the criteria. Conclusion: In summary, there is evidence for the efficacy of diets in chronic urticaria (CU) in individual individuals with clinical symptoms, but there is little evidence for the usefulness of systematic diets in CU due to a lack of systematic double-blind controlled trials. In our daily practice, we advocate asking patients whether they can identify any specific food allergies in their diet. If this is the case, we recommend following a tailored diet that excludes these identified food allergies. If not, we don't advocate any diets.